DAMPAK PENGELOLAAN PEMBANGUNAN TERHADAP KESADARAN BELA NEGARA MASYARAKAT DI DAERAH PERBATASAN INDONESIA-TIMOR LESTE - Siswanto, Dwi Joko; M. Sigit Saksono; Jarwono; Silitonga, Frangky; Titiek Herawati; Sopiin; Felik Leandro; Muhamad Andre Nuralam R (JURNAL MAHATVAVIRYA, 2024)
The strategic position of Indonesia's borders on the one hand can be a potential for cooperation between countries, but on the other hand it can be a threat to state defence and security. One form of potential that can turn into a serious threat is that there are still a number of border segments that have not been discussed and agreed with neighbouring countries. The threat can be in the form of aggression, territorial violations, armed rebellion, sabotage, espionage, acts of armed terror, sea and air security threats, and communal conflicts, Research Objectives, the purpose of this final project research is to find out the current management of development in Belu Regency. understand the phenomenon of what is experienced by research subjects such as behaviour, perceptions, actions and others, holistically and by way of description